2014
DOI: 10.1111/jep.12158
|View full text |Cite
|
Sign up to set email alerts
|

Minimal clinically important difference for change in comfortable gait speed of adults with pathology: a systematic review

Abstract: Changes in gait speed of 0.10 to 0.20 m s(-1) may be important across multiple patient groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
156
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(179 citation statements)
references
References 30 publications
10
156
3
2
Order By: Relevance
“…Previous studies reported clinically meaningful changes in walking speed in community-dwelling older adults for the 4-m walking test of 0.12 m/s (Perera et al 2006). More in general, small and substantial clinically meaningful changes in walking speed were reported from 0.05 to 0.10 m/s, respectively (Bohannon and Glenney 2014;Perera et al 2006). In this study, we found differences in walking speeds of 0.11 m/s for the 10-m compared to the 4-m walking test and 0.06 m/s for the 10-m compared to the 6-min walking test.…”
Section: Discussionsupporting
confidence: 44%
“…Previous studies reported clinically meaningful changes in walking speed in community-dwelling older adults for the 4-m walking test of 0.12 m/s (Perera et al 2006). More in general, small and substantial clinically meaningful changes in walking speed were reported from 0.05 to 0.10 m/s, respectively (Bohannon and Glenney 2014;Perera et al 2006). In this study, we found differences in walking speeds of 0.11 m/s for the 10-m compared to the 4-m walking test and 0.06 m/s for the 10-m compared to the 6-min walking test.…”
Section: Discussionsupporting
confidence: 44%
“…Besides having a significant post-intervention improvement and a medium effect size, the walking speed of the participants also improved by an average of 0.14m/s after intervention which is considered clinically important (minimal clinical important difference (MCID) = 0.10 - 0.17m/s). 42 The significant impact of the intervention on walking speed in BCS was expected, and corroborated the findings of previous multimodal PA intervention studies that focused on community-dwelling older adults. 43,44 The extent of improvement in walking speed could also potentially reduce the risk of falls.…”
Section: Discussionsupporting
confidence: 86%
“…Clinically important difference (CID) thresholds for these outcomes have been estimated at 1.0–3.0 mL/kg/min for VO 2peak , 5052 0.05–0.20 m/s for walking speed, 5358 and 20–50 m for the 6-minute walk test. 58,59 Thus, on average, AEX appears to have at least some clinically meaningful impact on these outcomes.…”
Section: Discussionmentioning
confidence: 99%